2017
DOI: 10.1080/0142159x.2017.1395002
|View full text |Cite
|
Sign up to set email alerts
|

Health providers’ communication skills training affects hypertension outcomes

Abstract: The brief communication skills training for health care providers appear to be an efficient way to improve patient-provider communication skills and hypertension outcome among patients with uncontrolled BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 33 publications
6
34
0
Order By: Relevance
“…Our results showed that socio-demographic variables had no significant effect on behavioral intention. Similar findings were reported previously which found that demographic characteristics exerted little effect on the intention behaviors [37, 40, 45].…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that socio-demographic variables had no significant effect on behavioral intention. Similar findings were reported previously which found that demographic characteristics exerted little effect on the intention behaviors [37, 40, 45].…”
Section: Discussionsupporting
confidence: 91%
“…Finally, in highlighting the socio-demographic attributes of the change patterns observed, our ndings demonstrate that ASHAs elder in age but with experience ≤12 years have increased probability of acquiring life skills and change in perceptions related to practice at personal, community, and workplace levels. This clearly a rmed the observation in the previous studies that health worker's performance is often related to increasing age and experiences regarding relations and power [15,26,27]. Greater probability of increased nancial literacy and self-con dence scores among ASHAs with more than 12 years of experience may re ect the need and outcome of savings in the last 10-12 years.…”
Section: Discussionsupporting
confidence: 81%
“…Differences in HL were found according to age group, education level and income ( 45 , 46 ). Consistent with the literature, the present study confirms that low HL is associated with low income ( 45 , 46 ) and income ( 47 ). Our findings were also consistent with reviews on the prevalence of HL in the United Kingdom and the USA, which reported older age was significantly associated with having limited HL( 44 ).…”
Section: Discussionmentioning
confidence: 96%